Photodynamic therapy in neurooncology - V. E. Olyushin; K. K. Kukanov; A. S. Nechaeva; S. S. Sklyar; A. E. Vershinin; M. V. Dikonenko; A. S. Golikova; A. S. Mansurov; B. I. Safarov; A. Y. Rynda; G. V. Papayan (Biomedical Photonics, 2023)
Literature review reflects the current status and development status of intraoperative photodynamic therapy in neurooncology and discusses the results of the most important studies on photodynamic  therapy (PDT). We searched the Pubmed, EMBASE, Cochrane Library and eLibrary data-bases for publications  published  between January 2000 and December 2022. Found 204 publications  in foreign sources and 59 publications  in domestic editions, dealing with the issues of photodynamic  therapy in neurooncology. An analysis of the literature has shown that intraoperative PDT in neurooncology is an important tool that contributes to increasing the radicality of the operation and local control. The basic rationale for the effectiveness of PDT lies in the study of the pathways leading to the complete devitalization of a malignant tumor, the study of the mechanisms of the local and systemic immune response. In addition, subcellular targets in PDT are determined by the properties of photosensitizers (PS). Second generation PSs have already been introduced into clinical practice. The effectiveness of PDT using photoditazine, 5-aminolevulinic acid has been demonstrated. The mechanisms of action and targets of these PS have been established. In Russia, a number of studies have repeatedly shown and proved the clinical effectiveness of PDT in groups of neurooncological patients with glial tumors and secondary metastatic tumors, but so far, the method has not been included in the clinical guidelines for the provision of high-tech neurosurgical care. There is certainly a need for further development of PTD techniques in neurooncology, especially in patients at high risk of recurrence and aggressive CNS tumors.